Prospective Evaluation of Opioid Consumption Following Cubital Tunnel Decompression Surgery. (January 2019) - Hozack, Bryan A.; Abboudi, Jack; Gallant, Gregory; Jones, Christopher M.; Kirkpatrick, William; Liss, Frederic E.; Rivlin, Michael; Takei, T. Robert; Wang, Mark L.; Silverman, Matthew; Foltz, Carol; Ilyas, Asif M.
Background: Managing postoperative pain is important for patients and surgeons. However, there is concern over opioid dependency. Cubital tunnel decompression is among the most common upper extremity surgeries. Our study aimed to analyze opioid use after cubital tunnel decompression to guide postoperative opioid prescribing.Methods: We prospectively collected opioid consumption for 16 consecutive months (February 2016 to June 2017) for cubital tunnel decompression patients. Data on demographics, insurance type, surgery performed, functional questionnaires (Quick Disabilities of the Arm, Shoulder and Hand [QuickDASH]), and electrodiagnostics (electromyography) were collected. Opioid consumption was reported at first postoperative visits.Results: One hundred patients consumed a mean of 50 morphine equivalent units (MEUs) (range, 0-300), or 7 oxycodone 5-mg pills, postoperatively. Cubital tunnel release (CuTR) patients consumed fewer than ulnar nerve transposition (UNT) patients (40.4 vs 62.5 MEUs or 5.4 vs 8.3 pills, P = .08). Patients undergoing submuscular UNT consumed more than CuTR (115.0 vs 40.4 MEUs or 15.3 vs 5.4 pills, p = 0.003) and more than subcutaneous UNT patients (37.8 MEU or 5.0 pills, p = 0.03). Medicare patients consumed less than privately insured (42.7 vs 54.1 MEUs, 5.7 vs 7.2 pills, P = .02) and less than workers' compensation patients (76.8 MEU or 10.2 pills, P = .04). Older patients consumed fewer than younger patients ( P = .03). Postoperative QuickDASH score was positively related to opioid intake ( P = .009).Conclusions: Patients consumed 7 oxycodone 5-mg pills after cubital tunnel decompression. Younger, privately insured, and workers' compensation patients, and those with worse functional scores and those undergoing UNT (specifically the submuscular technique) consumed more opioids.